Point-by-point fiber bragg grating inscription in free-standing step-index and photonic crystal fibers using near-ir femtosecond laser - Kalli, Kyriacos; Komodromos, Michael; Geernaert, Thomas; Nasiłowski, Tomasz; Urbańczyk, Wacław; Wójcik, Jan; Berghmans, Francis; Thienpont, Hugo; Koutsides, Charalambos (My University, 2010)
We report what we believe to be the first highly symmetric first-order IR femtosecond laser fiber Bragg gratings within the telecommunications C band in free-standing optical fiber, fabricated with a relatively low NA lens and without use of oil immersion techniques. This grating features the smallest dimensions for a pointby-point fiber grating reported so far (to our knowledge). This achievement paves the way to rapid mass manufacturing of highly efficient and stable Bragg gratings using ultrafast lasers in any type of fiber. Mastering this femtosecond grating inscription technique also allowed the fabrication of the first Bragg gratings with direct near-IR femtosecond inscription in photonic crystal fibers, and without the use of techniques that rely on the compensation of the holey structure.
Keywords: Fiber Bragg gratings; Bragg gratings; Grating inscription